A survey of flaviviruses in birds in green areas of São Paulo, Brazil - Lilian Dias Orico; Licia Natal Fernandes; Marcos Antônio Melo; Ticiana Zwarg; José Eduardo Levi; Mauro Toledo Marrelli (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract: INTRODUCTION: This study aimed to investigate Flavivirus infection in birds captured in green areas of São Paulo. METHODS: Oropharyngeal swabs, cloacal swabs, and blood samples from 170 birds captured in two green areas in São Paulo, Brazil were subjected to real time-polymerase chain reaction (RT-qPCR) analysis of Flavivirus specific NS5 gene fragment. RESULTS: All samples were negative for the presence of viral ribonucleic acid (RNA). CONCLUSIONS: Despite the negative results, Flavivirus surveillance must be performed regularly due to favorable ecological conditions for virus circulation and transmission among birds in these areas and their close proximity to humans.